Analisis Implementasi Kebijakan Satu Data Indonesia (SDI) di Pemerintah Provinsi Banten - Irawan, Syarrah; Handayani, Riny (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Presidential Regulation Number 39 of 2019 concerning One Data Indonesia aims to realize the availability of government data that is accurate, quality, up-to-date, and integrated with existing data, as well as easily accessible and shared between central and regional agencies. This research focuses on the Analysis of the Implementation of the One Data Indonesia (SDI) Policy in the Banten Provincial Government. This study aims to find out and analyze how the implementation of the One Data Indonesia (SDI) policy in the Banten Provincial Government. The problem researched by the researcher is that human resources in the Banten Provincial Government are not enough in the implementation of the One Data Indonesia policy in the Banten Provincial Government. This study uses a qualitative method by analyzing the results of observations, interviews and documentation. The results of the study were analyzed using the policy implementation theory put forward by George C. Edward III which showed that the implementation of the One Data Indonesia (SDI) policy in the Banten Provincial Government has not been running well completely. In terms of resources, there are still insufficient human resources and there are no functional positions of statisticians in the Banten Provincial Government, and improvements are still needed in terms of facilities. In terms of bureaucratic structure, there is no Standard Operating Procedure (SOP) in the implementation of One Data Indonesia in the Banten Provincial Government and sanctions for data producers in the SDI implementation stage that do not yet exist.